Studi Banding Paham Aqidah Mahasiswa Angkatan Tahun 2011 Fakultas Agama Islam Universitas Muhammadiyah Palangkaraya Terhadap Penyakit Tauhid Antara Sebelum dan Sesudah Mengikuti Pembelajaran Mata Kuliah Kemuhammadiyahan I: Comparative Study of 2011 Student Aqeedah Understanding at the Faculty of Islamic Studies, Muhammadiyah Palangkaraya University Against Tawhid Between Before and After Following Learning in Kemuhammadiyahan I Courses - Choiriyah, Ngismatul (Anterior Jurnal, 2013)
Participating in the study of Kemuhammadiyahan I courses This type of research uses descriptive qualitative research with 10 (ten) students who are students of the Islamic Religion Faculty of Muhammadiyah University Palangkaraya. The method of data collection uses observation, interviews, and documentation. While the data were analyzed using data collection steps, data reduction, data presentation and conclusions and verification. The results of this study are: First, the understanding of the aqidah of students before attending the Kemuhammadiyahan I course is still not purely from monotheistic diseases such as shirk, bid'ah, tahayul, tawassul, bid'ah and khurafat. Secondly, the understanding of Aqidah students after attending the Kemuhammadiyahan I course has already been purified from monotheistic diseases such as shirk, bid'ah, superstition, tawassul, bid'ah and khurafat. Third, there is a significant difference in the understanding of the students' aqid between before and after attending the Kemuhammadiyahan I course. This means that the material taught by the lecturer is effective and efficient enough so that there is a change of belief between before and after attending the Kemuhammadiyan I course.